Handgrip strength predicts leg power but not cardiorespiratory fitness in children - Alotaibi, Salem; Qaisar, Rizwan; Hussain, M. Azhar; Aljuhani, Osama; Alhussain, Maha H.; Marques, Diogo Luís; Marinho, Daniel Almeida; Alkahtani, Shaea A. (Frontiers in Physiology, 2025)
PurposeThe current study examined the ability of handgrip strength (HGS) to predict leg muscle power, cardiorespiratory fitness, and movement behaviors in children.MethodsOne hundred eighteen male children aged 10–13 years from primary and middle schools in Saudi Arabia were recruited for this cross-sectional study. Physical fitness tests included HGS, standing long jump (SLJ), and a 20-m shuttle run test (20mSRT). Daily movement behaviors (time spent on physical activity, sedentary activities, and sleep) were measured for seven consecutive days using accelerometers. A multiple linear regression analysis was conducted to analyze the ability of HGS to predict SLJ distance and 20 m SRT laps. Age and body mass index were also included in the model as covariates.ResultsHGS was significantly correlated with SLJ distance (r = 0.44, p < 0.05), 20mSRT (r = 0.22, p < 0.05), sedentary time (r = 0.34, p < 0.05), and moderate to vigorous physical activity time (r = −0.36, p < 0.05). In the regression models, HGS had a significant positive effect on predicting SLJ distance (β = 2.64, p < 0.001). Age was found to be a significant predictor of 20mSRT (β = 3.65, p < 0.001).ConclusionThese findings highlight that HGS may serve as a simple and practical indicator of musculoskeletal fitness, aiding early detection of functional limitations and informing physical development strategies in children Saudi boys, suggesting that HGS may be used to predict SLJ distance in this population.